1. Historical Evolution of Adagio (Analysis of the Choreographic Concept) - Todi Cristina (Sciendo, 2020)
By this study we propose to expose the steps that led to the development of the choreographic adagio. Without excluding the importance of the precursory period, the approach of the discourse introduces us into the middle of the 18th century, exactly in the age when this miracle of dancing began to assume clear contours. We remind of the entrées full of effects with high elevations of Auguste Vestris, the expressivity of Marie Salle, the Noverian manifesto certainly the pas de deux formula - which is used even nowadays - of Marius Petipa. The transformations of the subjects - from the mythology to the eternal theme of love - are completed by the different states of the danced dialogue. The deciphering of the symbols founding its gesticulation and explains the step or the choreographic element is visible through the scene of the balcony of ballet Romeo and Juliet by Prokofiev and by the meeting between Spartacus and Flavia in the ballet of Avram Haciaturian. The state of poetry, of dreaming, noble rise of the soul towards unsuspected horizons, the adagio, confesses to us its filiation even beyond the border of the age. We consider that this paper is useful both for the teaching staff who must instruct the youngsters in vocational schools a profound and qualitative choreographic culture, and to those who are training in the art of dance.